Safety and effectiveness of stereotactic radiosurgery for larger hemangioblastomas (>2cc): A multi-center retrospective study - Pavel S. Pichardo-Rojas; Salem M Tos; Georgios Mantziaris; Ahmed Shaaban; Ahmed M. Nabeel; Wael A. Reda; Sameh R. Tawadros; Khaled AbdelKarim; Amr M. N. El-Shehaby; Reem M Emad; Zhishuo Wei; Lindsay M. McKendrick; et al. (PLoS ONE, 2026)
Introduction Hemangioblastomas (HGB) are the most common primary intra-axial tumors in the posterior fossa in adults, with an overall occurrence of 7–10%. They occur sporadically or as part of von Hippel-Lindau (VHL) disease. The role of stereotactic radiosurgery (SRS) as a minimally invasive treatment in larger HGB (>2cc) has not been thoroughly investigated. Methods This multi-center study retrospectively analyzed data from 91 patients with large HGB (>2cc) treated between 1993 and 2023. Patients were stratified into VHL-associated and sporadic groups, with assessments including radiosurgical parameters, tumor response, overall survival (OS), and progression-free survival (PFS). Results Patients with VHL-associated HGB were younger at diagnosis (median: 33 years vs. 52 years, p < 0.001) and presented more frequently with multiple tumors (68.8% vs. 23.2%, p < 0.001). Cerebellar lesions were the most common location (70%), followed by brainstem lesions (21%). The median target tumor volume was smaller in VHL cases (3.49 cc vs. 6.5 cc, p = 0.038). Tumor control was achieved in 70% of cases across groups, with no significant differences in outcomes between VHL and sporadic cases. OS (170 months for VHL and 199 months for sporadic cases) and PFS (108 months for both groups) were comparable. Radiation necrosis was observed in 8.8% of patients. Conclusions SRS may provide favorable tumor control with low morbidity in both VHL-associated and sporadic cases of larger HGB (>2 cc).Future studies should compare SRS with resection for larger HGB and explore molecular predictors of favorable response to SRS.